The phytopathogen Xanthomonas campestris senses and effluxes salicylic acid via a sensor HepR and an RND family efflux pump to promote virulence in host plants - Kai Song; Ruifang Li; Ying Cui; Bo Chen; Lian Zhou; Wenying Han; Bo‐Le Jiang; Ya‐Wen He (mLife, 2024)
Abstract Salicylic acid (SA) plays an essential role in plant defense against biotrophic and semi‐biotrophic pathogens. Following pathogen recognition, SA biosynthesis dramatically increases at the infection site of the host plant. The manner in which pathogens sense and tolerate the onslaught of SA stress to survive in the plant following infection remains to be understood. The objective of this work was to determine how the model phytopathogen Xanthomonas campestris pv. campestris (Xcc) senses and effluxes SA during infection inside host plants. First, RNA‐Seq analysis identified an SA‐responsive operon Xcc4167–Xcc4171, encoding a MarR family transcription factor HepR and an RND (resistance‐nodulation‐cell division) family efflux pump HepABCD in Xcc. Electrophoretic mobility shift assays and DNase I footprint analysis revealed that HepR negatively regulated hepABCD expression by specifically binding to an AT‐rich region of the promoter of the hepRABCD operon, Phep. Second, isothermal titration calorimetry and further genetic analysis suggest that HepR is a novel SA sensor. SA binding released HepR from its cognate promoter Phep and then induced the expression of hepABCD. Third, the RND family efflux pump HepABCD was responsible for SA efflux. The hepRABCD cluster was also involved in the regulation of culture pH and quorum sensing signal diffusible signaling factor turnover. Finally, the hepRABCD cluster was transcribed during the XC1 infection of Chinese radish and was required for the full virulence of Xcc in Chinese radish and cabbage. These findings suggest that the ability of Xcc to co‐opt the plant defense signal SA to activate the multidrug efflux pump may have evolved to ensure Xcc survival and virulence in susceptible host plants.